THE INFORMAL MUSEOLOGY (Cadernos de Sociomuseologia, 2009)
No matter how elementary the level of attention that is paid to contemporary Museology in Portugal, its multifaceted character should nevertheless be acknowledged. It is a site where concepts, attitudes and aims cross, translating not only museology’s general guidelines, but the role and the place that the different actors in the most diverse processes seek to occupy in society, in the affirmation of the shared right to a full citizenship. The different forms of museology that has developed throughout the country, in particular post April 25, vouchsafes the statement that, in parallel with State museums, there came to light hundreds of museological processes by initiative of the cultural and ecological associative movements, in addition to those of the reinvigorated autonomous power. There are tens of thousands of people who, in various ways - more or less elaborated or theorised - find in museology the privileged expression means on issues concerning so many heritages – historical, architectural, linguistic, archaeological or anthropological - within the context of the valorisation and identification of local specificities and competences.